2019
DOI: 10.1039/c9ra04685b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically separable and reusable rGO/Fe3O4 nanocomposites for the selective liquid phase oxidation of cyclohexene to 1,2-cyclohexane diol

Abstract: A series of magnetically-separable and reusable rGO/Fe3O4 nanocomposites were successfully synthesized for the selective liquid-phase oxidation of cyclohexene to 1,2-cyclohexane-diol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…The strong interactions of Fe 3 O 4 nanoparticles with rGO can be illustrated by the formation of COFe bond. [ 45–48 ] The O 1s deconvoluted peak (Figure 3b) follows the same trend, where the deconvoluted peak at 530.1 eV is assigned to the OFe bond (lattice oxygen of (Fe 3 O 4 ). [ 45,46,49 ] The broad peak could be related to oxygen functionalities such as OCO, CO after the partial reduction of GO under laser irradiation.…”
Section: Resultsmentioning
confidence: 70%
“…The strong interactions of Fe 3 O 4 nanoparticles with rGO can be illustrated by the formation of COFe bond. [ 45–48 ] The O 1s deconvoluted peak (Figure 3b) follows the same trend, where the deconvoluted peak at 530.1 eV is assigned to the OFe bond (lattice oxygen of (Fe 3 O 4 ). [ 45,46,49 ] The broad peak could be related to oxygen functionalities such as OCO, CO after the partial reduction of GO under laser irradiation.…”
Section: Resultsmentioning
confidence: 70%
“…The corresponding equations were provided in the Supplementary material. (Pudukudy et al, 2019), while O1s (Figure 2c) peaks were ascribed to Fe3O4 (530.0 eV), C=O (531.5 eV) and C-O (532.8 eV) bonds (Guo et al, 2016). Moreover, Ca2p (Figure 2d, 347.6 eV, 351.2 eV) and P2p (Figure 2e, 133.1 eV, 133.8 eV) peaks (López et al, 2019;Lovón-Quintana et al, 2017) verified the presence of HAP in PMGO.…”
Section: Calculationmentioning
confidence: 69%
“…Graphene oxide (GO) has been reported to have more uniform dispersion in the synthetic magnetic materials (Fang et al, 2016). Furthermore, it is able to inhibit the selfpolymerization of Fe3O4 (Pudukudy et al, 2019). Thus, it has a broad application prospect in the field of magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe 2p spectrum of the Fe 3 O 4 /Ti 3 C 2 T x nanocomposites contained two main peaks at 710.4 and 723.4 eV belonging to the characteristic peaks of Fe 2+ and the other two peaks at 712.9 and 725.9 eV corresponding to the characteristic peaks of Fe 3+ (Figure S2B). , This indicated that the loaded iron oxide was Fe 3 O 4 . The above characterization results showed that the Ti 3 C 2 T x nanosheets and Fe 3 O 4 /Ti 3 C 2 T x nanocomposites have been successfully synthesized.…”
Section: Resultsmentioning
confidence: 86%
“…23−28 As for the Fe 3 O 4 /Ti 3 C 2 T x nanocomposites (Figure S1A), in characteristic peaks of Fe 3+ (Figure S2B). 30,31 This indicated that the loaded iron oxide was Fe 3 O 4 . The above characterization results showed that the Ti 3 C 2 T x nanosheets and Fe 3 O 4 / Ti 3 C 2 T x nanocomposites have been successfully synthesized.…”
Section: Resultsmentioning
confidence: 94%